2011
DOI: 10.1088/0953-8984/23/25/254204
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of a La-based bulk metallic glass: insight fromin situhigh-energy x-ray diffraction

Abstract: Constant-rate heating experiments using a fast x-ray camera (time resolution of 2.7 s) reveal detailed information about the thermal stability of La 62 Al 14 (Cu 5/6 Ag 1/6 ) 14 Ni 5 Co 5 (at.%) bulk metallic glass. Analyzing diffraction patterns in reciprocal space yields the thermal expansion of the amorphous alloy providing insight about the thermally activated relaxation effects and kinetics of the glass transition. The glass transition appears as a break in the value of the coefficient of volume thermal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…3a. The first peak position of the structure factor, Q 1 , corresponds to the length scale of medium-range order correlations in real space 29 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a. The first peak position of the structure factor, Q 1 , corresponds to the length scale of medium-range order correlations in real space 29 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the length scale of the structural transformation in the supercooled state is likely not less than the 4th shell distance (Z1 nm) and can be reflected in by Q 1 of S(Q) in reciprocal space (Fig. 3b), which is demonstrated to be more sensitive to medium/long range correlations 29 . It is hardly a coincidence that the length of the ideal face-centered-cubic (FCC)-like cluster-unit-cell for the medium-range order of Miracle's efficient cluster packing model 47 is calculated to be around 1.0-1.3 nm.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately due to technical problems part of the data acquired during the first cooling rate have been lost, without however affecting the presented results. As previously discussed, rapidly quenched metallic glasses keep excess free volume or internal stresses which can be released with the first annealing [10][11][12][13][14][15][16][17]. This phenomenology is due to the intrinsic kinetic nature of the glass transition, and the consequent dependence of Tg on the cooling rate [4,24].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenology is due to the intrinsic kinetic nature of the glass transition, and the consequent dependence of Tg on the cooling rate [4,24]. Assuming the atomic environments does not suffer important changes during the annealing, the position of the FSDP can be related to the relative volume change in the material as V/V0=(q0/q) 3 [14][15][16][17]. However, recently, it has been shown that for densely packed metallic glasses this interpretation is not unambiguous and other parameters, such as the FSDP intensity and width can give a clearer indication of the occurrence of structural changes [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation